PREVALENCE OF MORTALITY IN SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS-2 WITH DIABETES MELLITUS - ULLAH, T; SHEHZAD, J; AHMAD, A; REHMAN, AU; ULLAH, MT; ULLAH, A; ZEESHAN, M (Biological and Clinical Sciences Research Journal, 2024)
The coexistence of Diabetes Mellitus (DM) and COVID-19 has garnered considerable attention due to the elevated prevalence of DM among COVID-19 patients. Understanding the impact of DM on the severity of COVID-19 infections is imperative for effective treatment, given the challenges it poses across various healthcare systems. This study aimed to assess the frequency of Type II Diabetes Mellitus among symptomatic COVID-19-positive individuals and calculate the mortality rate among those diagnosed with Type II Diabetes Mellitus contracting COVID-19. Utilizing a cross-sectional approach, 142 samples were randomly selected for analysis to determine the prevalence of Diabetes Mellitus among individuals diagnosed with COVID-19. The findings revealed that out of the 142 COVID-19-positive individuals tested via RT-PCR, 66.2% were diabetic, while 33.8% were non-diabetic. Among the entire sample, 31% of patients succumbed to the infection, while 69.0% achieved full recovery. Specifically, within the diabetic group, 81.8% experienced mortality, with 59.2% recovering fully, whereas among the non-diabetic group, 18.2% passed away, and 40.8% recovered fully. The highest mortality rate was observed among individuals aged 60-74, comprising 45.1% of the total population under observation. The study underscores the elevated mortality risk associated with COVID-19 among diabetic individuals, with a mortality rate of 25.35%, significantly higher than the 5.63% mortality rate observed among non-diabetic individuals. Notably, the vulnerability to COVID-19 and increased mortality rates were particularly pronounced among individuals aged 45-74, with a notable emphasis on the heightened risk among those aged 60-74. Furthermore, the study found no significant disparity in mortality rates between male and female patients. These findings shed light on the heightened susceptibility of diabetic individuals to severe outcomes of COVID-19 and underscore the importance of targeted interventions and preventive measures, especially among the elderly diabetic population.